The Planktonic Relationship Between Fluid‐Like Electrodes and Bacteria: Wiring in Motion. Issue 4 (3rd January 2017) - Tejedor‐Sanz, Sara; Quejigo, Jose Rodrigo; Berná, Antonio; Esteve‐Núñez, Abraham
Abstract: We have explored a new concept in bacteria‐electrode interaction based on the use of fluid‐like electrodes and planktonic living cells. We show for the first time that living in a biofilm is not a strict requirement for Geobacter sulfurreducens to exchange electrons with an electrode. The growth of planktonic electroactive G. sulfurreducens could be supported by a fluid‐like anode as soluble electron acceptors and with electron transfer rates similar to those reported for electroactive biofilms. This growth was maintained by uncoupling the charge (catabolism) and discharge (extracellular respiration) processes of the cells. Our results reveal a novel method to culture electroactive bacteria in which every single cell in the medium could be instantaneously wired to a fluid‐like electrode. Direct extracellular electron transfer is occurring but with a new paradigm behind the bacteria–electrode interaction. Abstract : No strings attached : Microbial electrochemical devices have been considered to require the catalysis to be located at the electrode interface because of the need for microbial attachment. We show for the first time that a biofilm living mode is not a strict requirement for G. sulfurreducens to perform extracellular electron transfer to an anode.